Eterno ritorno o contemplazione del divenuto, astoricità o sovrastoria: Karl Löwith lettore di Nietzsche e Burckhardt (ACME, 2023)
Few thinkers – or perhaps none – occupy a position as relevant and strategic as Friedrich Nietzsche and Jacob Burckhardt in Karl Löwith philosophical historiography. Löwith’s contributions are therefore important in a double way: as scientific literature on each of these authors (and on their well-discussed relationship), as much as on Löwith’s theoretical thought. This paper will try to highlight this double significance by way of reconstructing two levels of interpretation, rather complementary instead of mutually exclusive. The first and more evident layer, which has often been proposed, will display Löwith’s interpretation as an existential passage from Nietzsche’s extremism to Burckhardt’s disenchanted moderation. On a second and less obvious layer, Löwith’s account seems to be able to structure Nietzsche and Burckhardt, at least potentially, as complementary inputs for an effective stance towards history and the historical world.